Multi-Center Analysis of Predictive Factors of Enteral Autonomy and Risk Factors of Complications of Pediatric Intestinal Failure in China - Jiang, Weiwei; Chen, Guanglin; Wang, Ying; Zhong, Wei; Zhou, Chonggao; Zhang, Jie; Lv, Xiaofeng; Du, Chunxia; Zhu, Zhongxian; Geng, Qiming; Tang, Weibing (Frontiers in Pediatrics, 2022)
Objectives: The aim of this study was to identify predictors for enteral autonomy and intestinal failure (IF)-related complications and evaluate the outcomes of a multi-center pediatric cohort in China. Methods: The medical records of pediatric patients with IF treated at various medical centers in China from January 1, 2012 to November 31, 2020 were retrospectively reviewed. Enteral autonomy was defined as sustained growth and cessation of parenteral nutrition for >90 days. Multivariate logistic regression analysis was used to identify factors predictive of enteral autonomy and the risk factors of complications, such as IF-associated liver disease (IFALD) and catheter-related bloodstream infection (CRBSI). Results: The study cohort of 92 pediatric patients with IF included 71 (77%) who underwent surgery and 21 (23%) who received non-surgical treatment. Eventually, 63 (68.5%) patients achieved enteral autonomy by the end of the follow-up period. Multivariate logistic regression analysis indicated that longer duration of parenteral nutrition (PN), sepsis, and non-breastfeeding were risk factors for enteral autonomy. When considering the detailed intraoperative data, the presence of an ileocecal valve (ICV) and greater residual small bowel (RSB) length were reaffirmed as predictors of achieving enteral autonomy. Medium/long-chain (MCT/LCT) lipids or sepsis were identified as negative predictors for IFALD. Univariate analysis revealed that the use of MCT/LCT lipids was associated with a greater likelihood of CRBSI. Conclusion: In this cohort, enteral autonomy was achieved at a moderate level, and the risk factors for not achieving enteral autonomy were a longer duration of PN, sepsis, and non-breastfeeding. The presence of ICV and a greater RSB length were important predictors of achieving enteral autonomy.